2015
DOI: 10.1002/cm.21219
|View full text |Cite
|
Sign up to set email alerts
|

Actin–myosin network influences morphological response of neuronal cells to altered osmolarity

Abstract: Acute osmotic fluctuations in the brain occur during a number of clinical conditions and can result in a variety of adverse neurological symptoms. Osmotic perturbation can cause changes in the volumes of intra- and extracellular fluid and, due to the rigidity of the skull, can alter intracranial pressure thus making it difficult to analyze purely osmotic effects in vivo. The present study aims to determine the effects of changes in osmolarity on SH-SY5Y human neuroblastoma cells in vitro, and the role of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Of particular interest are several genes with putative links to cytoskeleton organization (MYH13, MYO18, MYO3, TTBK2, PAK3; Table ) that are associated with signals of elevated divergence between upland and salt marsh populations of San Francisco Bay song sparrows. Previous work has shown that the cytoskeleton, which is responsible for maintaining cell morphology, is a likely candidate for regulating cell volume response in the face of osmotic changes (Di Ciano‐Oliveira et al, 2006; Bober et al., 2015). Cytoskeletal reorganization may allow cells to resist volume changes through the reinforcement of cell structure (Di Ciano‐Oliveira et al, 2006), a potentially important adaptation to salt water environments.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are several genes with putative links to cytoskeleton organization (MYH13, MYO18, MYO3, TTBK2, PAK3; Table ) that are associated with signals of elevated divergence between upland and salt marsh populations of San Francisco Bay song sparrows. Previous work has shown that the cytoskeleton, which is responsible for maintaining cell morphology, is a likely candidate for regulating cell volume response in the face of osmotic changes (Di Ciano‐Oliveira et al, 2006; Bober et al., 2015). Cytoskeletal reorganization may allow cells to resist volume changes through the reinforcement of cell structure (Di Ciano‐Oliveira et al, 2006), a potentially important adaptation to salt water environments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, shear stress applied to endothelial cells is transmitted via the cytoskeleton to the nucleus to induce changes in gene expression [ 15 ]. In addition, the cytoskeleton can regulate broader aspects of the mechanoresponse, such as constraining swelling of neuronal cells in response to osmotic stress [ 16 ]. In iPSCs specifically, hyperosmolarity also induces remodeling of cytoskeletal actin [ 17 ].…”
Section: Introductionmentioning
confidence: 99%